Accounting Fundamentals for Non-Accountants (Book). - Hendrickson, Harvey S.; Rockness, Joanne W. (The Accounting Review, 1985)
Abstract Reviews the book "Accounting Fundamentals for Non-Accountants," by Stephen A. Moscove.